Poslali nám to k posouzení - Hrdlička, Milan (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2018)
In prepositional clauses of purpose (ADV Fin), a whole range of primary and secondary prepositions are used. Their speech distribution rules are complex, particularly in the case of the original prepositions which are virtually missing semantics. The most frequently used are pro+Ak, na+Ak and k+D, which in some context can be synonymous (materiál pro/na/k opravu/ě střechy). Besides other cases, the preposition pro+Ak is used to express address (Přinesl to pro děti), na+Ak is used with deverbatives (Dal jim to na hraní, na psaní) as well as with a wide range of nouns in general (Jeli tam na rekreaci), k+D comprises nouns expressing a mental activity (Poslali jim to k rozboru), za+Instr refers to relocation with the aim of contact (Vydal se do ciziny za zkušenostmi). Nonetheless, many examples arise from language usage, and thus foreigners find them difficult to learn.
They sent for us for review
Keywords: preposition; adverbial clause of purpose; adverbial clause of reason; meaning; synonymy; usage